Does human capital protect workers against exogenous shocks? South Africa in the 2008 - 2009 crisis - Ron Leung; Marco Stampini; Désiré Vencatachellum (Institute for the Study of Labor (IZA), 2009)
The financial and economic crisis of 2008 and 2009 has taken its toll on the South African economy. The economy contracted for the first time since 1998, and entered recession during the fourth quarter of 2008. The GDP contraction was soon transmitted to the labor market. Between the second quarters of 2008 and 2009, employment fell by 3.8 percent. However, not all individuals were hit with the same intensity. Using labor force survey data unique in the African context, we find that human capital provided a buffer against the shock. After controlling for observable characteristics, education and experience showed the potential to entirely offset the effect of the recession on the likelihood of employment. This has important policy implications, as it strengthens the case for strategic investments in human capital, and helps identifying the unskilled as those with the highest need for social safety net interventions during the recession.
Keywords: J2; E3; 330; Labor markets; South Africa; financial crisis; human capital; business cycle; emerging economies; Arbeitslosigkeit; Humankapital; Qualifikation; Konjunkturelle Arbeitslosigkeit; Finanzmarktkrise; Schock; Südafrika